Islam and the University Curriculum: Experiences of Teaching and Learning in Higher Education (American Journal of Islam and Society, 2014)
This special academic event was organized by the Sociology of Religion(Socrel) Study Group of the British Sociological Association in London on December7, 2013. One of its main objectives was to discuss, in the light of negativepublicity and the increasing number of Muslim students pursuing certainprofessions, whether “Islam” as a module or a course has been adequatelywoven and integrated into the university teaching and learning contexts.The organizers, Socrel chair Abby Day (Department of Sociology, Goldsmiths,University of London) and Sarah-Jane Page (School of Languages andSocial Sciences, Aston University), sought answers to the following questions:To what extent are higher education institutions responding to this relationship?How do Muslim students feel that Islam is represented in higher education?Does a Christianized curriculum still dominate the way these courses are designed?How do non-Muslim students respond to the content of courses thatmainly deal with Islam and Muslims? How do teachers respond to a more diversestudent body that hails from various socio-cultural backgrounds?Sociologists of religion have realized the importance of reflecting criticallyupon the study and teaching of religion. Publications such as Robert Orsi’s editedThe Cambridge Companion to Religious Studies (New York: CambridgeUniversity Press, 2012) has paid attention to these and related aspects. A qualitativeshift of scholary endeavors has been noted; scholars and researchershave now turned their lenses to specific religious traditions that have comeunder the spotlight because of their adherents’ apparent “violent” acts. Since9/11, Islam and Muslims have naturally become one of the targeted traditions(see “The Muslim World after 9/11,” Rand report at www.rand.org).This scholarly attention has resulted in the spread of Islamophobia in westernEurope and elsewhere, not to mention the gradual securitization of Muslimcommunities. This latter development seems to have enormous implicationsfor the academic arena where courses/modules on aspects of “Muslim extremism”in countries such as the United Kingdom have been closely watched and ...